Autoimmune rheumatic diseases in the intensive care unit: experience from a tertiary referral hospital and review of the literature (2005)
Autoimmune rheumatic diseases (AIRD) are not uncommon in the general population and up to one third of hospitalized patients with AIRD may need admission to intensive care unit (ICU). This paper describes the causes of admission, the clinical features and outcome of 24 AIRD patients admitted to a medical ICU from a third level hospital. Thirteen patients had systemic lupus erythematosus (54.2%), three rheumatoid arthritis (12.5%), three pulmonary renal syndrome (12.5%), two dermatopolymyositis (8.3%), two scleroderma (8.3%) and one antiphospholipid syndrome (4.2%). The main causes for ICU admission were rheumatic disease flare-up (37.5%), infection (37.5%) and complications derived from rheumatic disease (29.1%). Mortality during ICU stay was 16.7% (four patients). Excluding shock requiring vasopressor support, no statistical difference was found between survivors and nonsurvivors; although there was a trend to higher test severity scores (APACHE II, ODIN) in nonsurvivors. Our results reveal a lower mortality rate in AIRD patients admitted to the ICU than reported previously. Severity scores such as APACHE II are predictors of mortality in patients with AIRD in the ICU.